Isolation and Optimization of Phages Infecting Members of the Streptococcus bovis/Streptococcus equinus Complex - Jenny Laverde Gomez; Cory Schwarz; Marina Tikhonova; Clark Hamor; Yizhi J. Tao; Pedro J. J. Alvarez; Jacques Mathieu (Applied Microbiology)
Background: Cattle production is a cornerstone of U.S. agriculture but faces increasing pressure to balance profitability with environmental sustainability. Optimizing the ruminal microbiome to enhance feed efficiency could help address both challenges. Members of the Streptococcus bovis/Streptococcus equinus complex (SBSEC) are key contributors to ruminal acidosis and related digestive disorders due to their role in carbohydrate fermentation and lactic acid production. Bacteriophages targeting this bacterial group present a promising approach to mitigate this problem with high precision and without promoting the spread of antibiotic resistance. Methods: A collection of SBSEC-targeting bacteriophages were isolated from cattle rumen fluid and feces and further characterized. Characterization included host-range evaluation, whole genome sequencing, and growth inhibition assessment via optical density measurements. Selected bacteriophages underwent training to enhance infectivity. Results: Eleven lytic and one lysogenic phage were isolated. Several phages demonstrated sustained bacterial growth suppression, showing efficacy against SBSEC bacteria from diverse sources despite narrow host ranges. Co-evolutionary training was done in a subset of phages to improve bacteriolytic activity but had an inconsistent effect on the ability of phages to inhibit the growth of their naïve host. Genomic sequencing and phylogenetic analysis revealed uniqueness and clustering into three distinct groups that matched phenotypic characteristics. Conclusions: This study demonstrates the potential of bacteriophages as precise biological control agents, with successful isolation and enhancement of phages targeting SBSEC bacteria. Eleven lytic genome-sequenced phages show promise for development as cattle feed additives, though further research is needed to optimize their application in agricultural settings.